1968
DOI: 10.3402/tellusa.v20i3.10023
|View full text |Cite
|
Sign up to set email alerts
|

On the size distribution of water soluble particles in the atmosphere

Abstract: The size distribution of the mass concentration of some water soluble materials was measured by an impactor of three stages and membrane filters. It was found that about the half of the mass of sulfate and ammonium particles is in the range of Aitken nuclei. The size distribution of sulfate particles depends on the relative humidity of the air: more nuclei are in the Aitken size range if the relative humidity is smaller. The size distribution of chloride particles is rather different from that of sulfate and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
4
5
0
Order By: Relevance
“…The size distributions of chloride and sodium were approximately log-normal and were in good agreement with mode B of the curve for total aerosol. This observation indicates that chloride and sodium are mostly present in the giant size range, which is in agreement with the reported findings by other investigators (Junge, 1963;Meszaros, 1968).…”
Section: Chloride and Sodiumsupporting
confidence: 94%
“…The size distributions of chloride and sodium were approximately log-normal and were in good agreement with mode B of the curve for total aerosol. This observation indicates that chloride and sodium are mostly present in the giant size range, which is in agreement with the reported findings by other investigators (Junge, 1963;Meszaros, 1968).…”
Section: Chloride and Sodiumsupporting
confidence: 94%
“…Figure 4 show that particle size distributions of Na ÷ and C1-correlates very well at the various sites and during the different monitoring periods, indicating that both ions are mainly produced by the same source, most likely marine aerosols. These ions are mostly present in the coarse size range, which is in agreement with the findings of other authors (Junge, 1963;Mrsz~iros, 1968;Khemani et al, 1982;Savoie and Prospero, 1982).…”
Section: Rainy Seasonsupporting
confidence: 82%
“…Further, data on the chemical composition of small particles around 0.02*m are at present insufficient compared with that of larger particles. Therefore, it is difficult as yet to make clear why these small particles showed a reduced value of e. Meszaros (1968) reported that the ratio of the mass of soluble material to that of insoluble material in particles in the size range of r* 0.14*m was greater than that for particles in the size range of r>0.14pm as shown in Fig. 5.…”
Section: Discussionmentioning
confidence: 98%
“…5 shows the values of * thus obtained as a function of dry radius rd. The values of soluble fraction obtained by Meszaros (1968) is also shown in the figure. The broken lines indicate the roughly estimated mean values as a function of particle radius.…”
Section: Growth O F Atmospheric Aerosolsmentioning
confidence: 94%
See 1 more Smart Citation